Marchantiophyta Family Radulaceae in Batang Toru Forest, North Sumatra Indonesia - Damanik, Risjunardi; Pasaribu, Nursahara; Siregar, Etti Sartina; Syamsuardi, S (Universitas Muhammadiyah Surakarta, 2024)
The diversity of liverworts in North Sumatra is currently limited, highlighting the need for further investigations. Therefore, this study aims to collect and determine data on the liverworts of the Radulaceae family in the Batang Toru forest of North Sumatra. This forest was selected because it has very high rainfall with suitable humidity for the growth of liverworts. The samples were collected using an exploratory survey method, namely by collecting all the liverworts of the Radulaceae family along the Batang Toru forest hiking trails. The results showed 17 species of which three are new records for Sumatran liverworts namely Radula iwatsukii, Radula kinabaluensis and Radula obscura. The Radulaceae family was found as epiphytes on tree trunks and leaves. Based on the number of specimen collections, the most commonly found species was Radula javanica. In addition, Radulaceae in the Batang Toru forest was spread at altitudes between 800 and 1100 m.a.s.l and can be included in the Lower Montane Forest category.